Les etrangers en France. Avec la participation de: Ch. Ageneau, H. Barthélemy, H. Bartoli [e.a. Introd. de J.-M.D. (=J.M. Domenach)]
Avec bibliogr., graphs et tabs. Esprit. Nouvelle série. 1966, avril.